PENGEMBANGAN PENDIDIKAN BERBUDAYA NIRKEKERASAN DI MADRASAH IBTIDAIYAH SE-KABUPATEN JEMBER - Nino Indrianto; Zainuddin Al-Haj Zaini; Nina Hayuningtyas (Pendidikan Guru Madrasah Ibtidaiyah (PGMI), 2019)
The number of violence in the education environment is still a problem for education in Indonesia. Madrasah as part of the national education system must be able to provide solutions to these problems. The development of non-violent culture education is expected to be able to provide solutions, so that produces some graduates who have self-control, noble character and have a sense of togetherness as one nation and country. This research aimed to determine prevention and control efforts and also the sanctions against perpetrators of violence in realizing a non-violence culture at MIN 1 and MIN 6 Jember. This type of research was qualitative research with sampling techniques using purposive sampling. Furthemore, the methods used to collect data were  documentation, interviews, and observation. The results of this research indicated that: 1) MIN 1 Jember undertook preventive measures by making activities that can build communication among the members of madrasah, while MIN 6 Jember took preventive action efforts by making activities that can build closeness among the members of madrasah, 2) MIN 1 and MIN 6 Jember ,in efforts to deal with violence, followed up the violence cases propotionally, 3) MIN 1 and MIN 6 Jember gave the sanctions or punishments to the perpetrators of violence verbally, writtenly, and other educational sanctions.